2017
DOI: 10.1111/hae.13372
|View full text |Cite
|
Sign up to set email alerts
|

Influence of medical insurance schemes and charity assistance projects on regular prophylaxis treatment of the boys with severe haemophilia A in China

Abstract: Objective: To explore the influence of medical insurance policy and charity assistance projects on the uptake and discontinuation of regular prophylaxis treatment in Chinese severe haemophilia A children.Methodology: This retrospective study was conducted on children with severe haemophilia A, who received FVIII prophylaxis treatment at 12 haemophilia centres in China

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…In 2017, the Haemophilia Experience, Results and Opportunity (HERO) study compared quality of life of PWH in China with nine other countries; results showed that PWH in China had lower rates of employment, prophylaxis treatment, and experienced greater difficulties in obtaining replacement factors, and timely treatment 48 . Furthermore, although the overall proportion of reimbursement for haemophilia has improved, it is not consistent across provinces/locations and has been reported, ranges from 40% to 94% 16 . This is because specific provisions for medical insurance are formulated and executed at the local government levels, and the reimbursement proportion is usually lower in those economically less developed provinces/locations.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2017, the Haemophilia Experience, Results and Opportunity (HERO) study compared quality of life of PWH in China with nine other countries; results showed that PWH in China had lower rates of employment, prophylaxis treatment, and experienced greater difficulties in obtaining replacement factors, and timely treatment 48 . Furthermore, although the overall proportion of reimbursement for haemophilia has improved, it is not consistent across provinces/locations and has been reported, ranges from 40% to 94% 16 . This is because specific provisions for medical insurance are formulated and executed at the local government levels, and the reimbursement proportion is usually lower in those economically less developed provinces/locations.…”
Section: Discussionmentioning
confidence: 99%
“…The increase in the reimbursement ratio and extension of health insurance coverage for haemophilia since 2004 represent an important milestone for PWH in China. A retrospective study of 12 centres in China showed that with the improvement of local medical insurance policies, the average duration of prophylaxis received by children with haemophilia increased from 16.7 weeks in 2008 to 32.8 weeks in 2012 16 …”
Section: Achievements In Capacity Building and Development Of A Haemomentioning
confidence: 99%
See 1 more Smart Citation
“…Other important QoL parameters such as education and employment attendance, community engagement, as well as patient‐reported outcomes will need to be assessed in future studies. Third, the initiation and the length of prophylaxis were heterogeneous, when and how long the patient would be on prophylaxis mainly depended on their ability to afford the out‐of‐pocket payment beyond their insurance coverage 28 . It is noteworthy that no children had prophylaxis beyond 30 months over the 6‐year (72‐month) period and that the points of time of actual initiation of prophylaxis varied.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported by Yu et al 23 A major reason was the lower reimbursement rates for NRCMS compared with URBMS. Li et al 24 explored the influence of medical insurance policy on the regular prophylaxis treatment in Chinese children with severe hemophilia A and found groups receiving higher reimbursement proportion were more likely to have higher medication consumption. Similarly occurs for corrective surgery, which costs have increased substantially with the application of advanced technology such as pedicle screw constructs, blood salvage techniques, and intraoperative cord monitoring.…”
Section: Discussionmentioning
confidence: 99%